An overview on ceramic multi-material additive manufacturing: progress and challenges - Yifei Li; Annan Chen; Jin Su; Yinjin Li; Yue Zhang; Zhaoqing Li; Shixiang Zhou; Jinhan He; Zhaowenbo Cao; Yusheng Shi; Jian Lu; Chunze Yan (International Journal of Extreme Manufacturing)
Additive manufacturing (AM) offers the unique capability of directly creating three-dimensional complicated ceramic components with high process flexibility and outstanding geometry controllability. However, current ceramic AM technology is mainly limited to the creation of a single material, which falls short of meeting the multiple functional requirements under increasingly harsh service circumstances. Ceramic multi-material additive manufacturing (MMAM) technology has great potential for integrally producing multi-dimensional multi-functional components, allowing for point-by-point precision manufacturing of programmable performance/functions. However, there is a huge gap between the capabilities of the existing ceramic MMAM technology and the requirements for industrial application. In this review, we discuss and summarize the research status of ceramic MMAM technology from the perspectives of feedstock selection, printing process, post-processing, component performance, and application. Throughout the discussion, the challenges associated with ceramic MMAM such as heterogeneous material coupled printing, heterogeneous interfacial bonding, and co-sintering densification have been put forward. This review aims to bridge the gap between AM technologies and the requirements for multifunctional ceramic components by analyzing the existing limitations in ceramic MMAM and pointing out future needs.